O-022 Pre-radiosurgical embolization of arteriovenous malformations: a single institution review. (4th July 2012) - Santarelli, J; Steinberg, G; Do, H; Dodd, R; McTaggart, R; Marcellus, M; Adler, J; Chang, S; Marks, M
Abstract : Background: Multimodality therapy for brain AVMs utilizing embolization followed by radiosurgery is controversial. We present the results of the largest case series to date of patients who have undergone AVM embolization followed by radiosurgery, in order to evaluate cure rates and complications using this modality of therapy. Methods: A retrospective review of our institutional AVM database was performed, identifying 95 patients over an 11-year period (1997–2008) who underwent dual modality treatment. Patients previously treated with either surgery or radiosurgery prior to embolization were excluded, as were patients who underwent scheduled surgical treatment following embolization. Pre- and post-treatment AVM volumes were assessed using angiography. Post-radiosurgical treatment volumes were assessed using angiography (41%) or MRI (59%). Only those patients with >3-year post-radiosurgical follow-up were included in this analysis. Results: Mean AVM volume pre-embolization was 26 ml and declined to 15 ml post-embolization. Mean modified Pollock-Flickinger score pre-embolization was 3.4 and post-embolization was 2.2. 59 patients had adequate follow-up for inclusion in our study. 34 patients (58%) achieved AVM obliteration within 3 years of treatment, without neurological decline. 23 patients had residual at 3 years. Two patients died in the follow-up period. Excellent outcome was accomplished in 100% of patients with modified Pollock-Flickinger score 2. Conclusion: Pre-radiosurgical embolization of brain AVMs in our series appears to improve the rate of excellent outcome (obliteration following radiosurgery, without change in modified Rankin score). Competing interests: None.